Moodle in the Algerian EFL Classroom: Practical Considerations - GHOUALI, Kamila; BENMOUSSAT , Smail (Journal of Human Sciences, 2020)
Following Hutchinson and Waters’ (1987) model of needs analysis, the study tried to identify students’ wants, necessities and lacks that were existing at the level of assessment in the writing module at the English Department at Tlemcen University. It tried to demonstrate the importance of using Moodle for the sake of meeting those needs. To achieve these aims, a questionnaire was administered to 35 first-year students. The results revealed that students needed more writing sessions, practice, feedback, teacher-learner interaction, self-assessment, formative assessment, remedial work and diagnosis. They also needed to have a relaxing, motivating, attractive, and up-to-date 21st century evaluation that would help them, accurately, be aware of their mistakes and writing problems in an organized manner. Moodle, as an alternative assessment method, can meet those needs due to the large features it offers with regard to the evaluation.